2003
DOI: 10.1002/jcp.10320
|View full text |Cite
|
Sign up to set email alerts
|

Codominance of cisplatin resistance in somatic cell hybrids

Abstract: Intrinsic or acquired resistance to cisplatin in cancer cells remains a major obstacle to successful chemotherapy. The clinically relevant genetic and molecular mechanisms of resistance have not yet been identified. Cisplatin-resistant (CP-r) human KB epidermoid carcinoma cell lines (HeLa) resistant to varying levels of cisplatin after single and multiple selection steps are cross-resistant to other platinum compounds and to methotrexate. Intraspecies hybrids of the sensitive and KB CP-r cells were fused with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Our previous research demonstrated that the cellular proliferation rate is reduced with increasing cisplatin resistance in CP-r cells (10). The utilization of glucose has been recognized as an important feature of tumor development.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous research demonstrated that the cellular proliferation rate is reduced with increasing cisplatin resistance in CP-r cells (10). The utilization of glucose has been recognized as an important feature of tumor development.…”
Section: Resultsmentioning
confidence: 99%
“…Processes that require energy, such as fatty acid synthesis, protein synthesis, and cell growth are curtailed in CP-r cells (9, 10, 32), possibly through the effects of SIRT1 as a central modulator. Overexpressed SIRT1 in CP-r cells might result in a higher threshold for apoptosis by targeting numerous cellular factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the relatively slower growth rate of CP-r cells appears to be dominant. In the two-step CP-r KB cell line, KB-CP1, resistance is no more dominant than in the single-step CP-r KB cell line, KB-CP.5, suggesting that one of the two steps of resistance in KB-CP1 may be less dominant or recessive [20]. These dominance data suggest that it might be possible to identify one or more genes responsible for cisplatin resistance by gene transfer from a resistant cell line to a sensitive cell line.…”
Section: Dominant Gene(s) Responsible For Cisplatin Resistancementioning
confidence: 94%
“…In an attempt to understand and eventually isolate the gene(s) involved in cisplatin resistance, intraspecies hybrids have been formed between CP-s and CP-r KB epidermal carcinoma cells to determine whether cisplatin resistance is a dominant or recessive genetic trait [20]. The parental control KB-3-1 CP-s cell line, the single-step CP-r cell line (KB-CP.5), and a two-step resistant cell line (KB-CP1), respectively, were fused with a cisplatin sensitive cell line (HeLa D98 OR ), which is resistant to ouabain but sensitive to hypoxanthine-aminopterin-thymidine (HAT).…”
Section: Dominant Gene(s) Responsible For Cisplatin Resistancementioning
confidence: 99%